Clinical results and complications in patients Operated for colloid cyst (Annals of Medical Research, 2021)
Aim: The present study aimed to report the peri- and postoperative complications in patients undergoing third ventricular colloid cyst resection using a microsurgical approach.Materials and Methods: A total of 29 patients with symptomatic third ventricular colloid cysts were operated upon via the microsurgery method at two different neurosurgery clinics, and their data were analyzed retrospectively.Results: Among them, 12 (41.4%) were men, and 17 (58.6%) were women. The mean age was 34.24 ±16.43 years, and the age range was 1–70 years. Headache was the most common symptom at reference and occurred in 21 (72.4%) patients. Also, ataxia was the presenting symptom in 7 (24.1%) of our patients, vomiting in 6 (20.7%), visual loss in 6 (20.7%), epileptic seizures in 4 (13.8%), incontinence in 4 (13.8%), and loss of consciousness in 1 (3.4%). Moreover, 19 (65.5%) had hydrocephalus, and two of them with weak consciousness were operated after the application of a preoperative external ventricular drainage systemConclusion: The interhemispheric transcallosal approach is the most commonly used method in colloid cyst microsurgery, and the most frequent surgical complication is venous infarction secondary to this approach. Thus, the significant results of infarct that occurred in patients with preoperative hydrocephalus suggest that this complication could be controlled more easily if the hydrocephalus and intracranial pressure are followed up more carefully in the pre- and perioperative periods.
Keywords: Colloid cyst; complication; hydrocephalus; transcallosal; venous infarction